Salivary glucose concentration exhibits threshold kinetics in normal-weight, overweight, and obese children - Hartman ML (Dove Medical Press, 2014)
Mor-Li Hartman,1 J Max Goodson,1 Roula Barake,2 Osama Alsmadi,3 Sabiha Al-Mutawa,4 Jitendra Ariga,4 Pramod Soparkar,1 Jawad Behbehani,5 Kazem Behbehani,6 Francine Welty7 1Department of Applied Oral Sciences, The Forsyth Institute, Cambridge, MA, USA; 2Department of Nutrition, The Dasman Diabetes Institute, Dasman, Kuwait; 3Genome Center, The Dasman Diabetes Institute, Dasman, Kuwait; 4Ministry of Health, Kuwait City, Kuwait; 5Faculty of Dentistry, Kuwait University, Kuwait City, Kuwait; 6The Dasman Diabetes Institute, Dasman, Kuwait; 7Division of Cardiology, Beth Israel Deaconess Medical Center, Boston, MA, USA Background: Metabolic syndrome in childhood predicts the development of cardiovascular disease and type 2 diabetes (T2D) in adulthood. Testing for features of metabolic syndrome, such as fasting plasma glucose concentration, requires blood sampling which can be difficult in children. Here we evaluated salivary glucose concentration as a surrogate measurement for plasma glucose concentration in 11-year-old US children. Methods: Children from Portland, Maine, and Cambridge, Massachusetts, with a mean age of 10.6±0.2 years provided 6-hour fasting samples of both blood and whole saliva. Salivary glucose levels were measured with a high-sensitivity assay (sensitivity =0.002 mg/dL). Plasma glucose levels were determined by a commercial clinical laboratory. Blood pressure, salivary flow rate, height, and weight were also measured. Results: Of the 65 children enrolled, there were two underweight children (3.1%), 30 normal-weight children (46.2%), 12 overweight children (18.4%), and 21 obese children (32.3%). The mean overall glucose concentrations were 0.11±0.02 mg/dL in saliva and 86.3±0.8 mg/dL in plasma, and these did not differ significantly by body–weight groups. By regression analysis, the plasma concentration equaled 13.5 times the saliva concentration, with a threshold level of 84.8 mg/dL. Salivary glucose values less than threshold plasma concentration were essentially zero. Diagnostic analysis indicated a positive predictive value of 50%, a negative predictive value of 90%, and a sensitivity and specificity both of approximately 75%. The salivary glucose concentration did not vary with saliva flow rate. Conclusion: Taking into account the threshold response characteristics of the salivary glucose concentration response, these results suggest that testing salivary glucose levels may be useful as a screening assay for high fasting plasma glucose levels. The low false positive value is important to assure a low fraction of missed diagnoses. Keywords: saliva, salivary glucose, plasma glucose, children